The incidence and economic burden of injuries in the United States - Finkelstein, Eric.; Corso, Phaedra S.; Miller, Ted R. (New York ; Oxford : Oxford University Press, 2006)
Useful for public health practitioners, researchers and students, this book provides a look at the incidence and economic burden of injuries. Chapter topics include incidence by detailed categorisations, lifetime medical costs and productivity losses as a result of injuries, and a discussion of trends.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wounds and injuries -- Economic aspects -- United States; Accidents -- Economic aspects -- United States; Wounds and injuries -- United States -- Statistics; Accidents -- United States -- Statistics